The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1055/s-0037-1615747
|View full text |Cite
|
Sign up to set email alerts
|

Time Spent on Dedicated Patient Care and Documentation Tasks Before and After the Introduction of a Structured and Standardized Electronic Health Record

Abstract: Implementation of a structured and standardized EHR was associated with 8.5% decrease in time for dedicated patient care during consultations in one center and 8.3% increase in dedicated documentation time in another center. These results are in line with physicians' concerns that the introduction of a structured and standardized EHR might lead to more documentation burden and less time for dedicated patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 8 publications
3
71
0
Order By: Relevance
“…Third, our findings suggest that clinical practices and health-care systems must continue to explore technologies that facilitate inter-physician communication. Many researchers have shown that adoption of EHRs shifts the amount of time traditionally spent in a variety of aspects of patient care [12][13][14], an early manuscript demonstrated that emergency room physicians were eager to use electronic modalities to communicate with community-based colleagues [15], and several authors have demonstrated that use of an EHR can improve the quality and efficiency of discharges from inpatient services and of communications between physicians, nurses, and pharmacists [16][17][18]. However, only one study to our knowledge has shown that adoption of electronic technologies-specifically, a computerized referral platform-enhances quality or frequency of inter-physician communications [19], and our data may support that notion.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our findings suggest that clinical practices and health-care systems must continue to explore technologies that facilitate inter-physician communication. Many researchers have shown that adoption of EHRs shifts the amount of time traditionally spent in a variety of aspects of patient care [12][13][14], an early manuscript demonstrated that emergency room physicians were eager to use electronic modalities to communicate with community-based colleagues [15], and several authors have demonstrated that use of an EHR can improve the quality and efficiency of discharges from inpatient services and of communications between physicians, nurses, and pharmacists [16][17][18]. However, only one study to our knowledge has shown that adoption of electronic technologies-specifically, a computerized referral platform-enhances quality or frequency of inter-physician communications [19], and our data may support that notion.…”
Section: Discussionmentioning
confidence: 99%
“…7 Despite documentation becoming more comprehensive with the switch from paper to electronic medical records, it has also likely increased the amount of time spent documenting. [8][9][10] The problem is amplified when treating patients with chronic conditions, for whom providing guideline-based care in all scenarios would take more time than the practicing physician has available for patient care. 11 Considering 67.7% of patients 65 years or older have at least two chronic conditions in 2015, this issue is particularly significant with the aging U.S. population.…”
Section: Background and Significancementioning
confidence: 99%
“…1,2 Many physicians have reported generally positive experiences with EHRs, 3 but despite the documented benefits of such systems, 4 EHR systems are also associated with unintended increases in physician workload and documentation times, [5][6][7][8] hospital inefficiencies, 9 and decreased time spent delivering direct patient care. [10][11][12][13] EHR-related increases in physicians' documentation and billing workload are key contributors to physician dissatisfaction in the field of neurology, where physician burnout is high relative to other specialties, [14][15][16] thereby potentially leading to compromises in patient-care quality. 17,18 As a specialty, neurology entails high-EHR utilization due to several factors.…”
Section: Background and Significancementioning
confidence: 99%